Figure 13 in A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species - Wilbert, Norbert; Song, Weibo (Zenodo, 2008)
Figure 13. Euplotes balteatus (A–D), Euplotes petzi nov. spec. (E–H) and Euplotes rariseta (I– N) after protargol impregnation. (A–C) Ventral view of three specimens, to show the general appearance of infraciliature, arrow in A marks the strong and loosely arranged transverse cirri, arrowheads in C indicate the two marginal cirri. (D) Dorsal view, note that the basal bodies are loosely arranged. (E, G, H) Ventral view, note the two small and closely- spaced marginal cirri (arrow and arrowheads). (F) Dorsal view. (I, K) Ventral view, arrows mark the single marginal cirrus, arrowheads in K indicate the weak and close-set transverse cirri. (L) Ventral view, arrowhead marks the two anteriormost frontoventral cirri. (M) Ventral view, to show the adoral zone and the marginal cirrus (arrowhead). (N) Ventral view, arrow indicates the paroral membrane. Scale bars: 20 Mm (A, I); 35 Mm (E). : Published as part of Wilbert, Norbert & Song, Weibo, 2008, A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species, pp. 979-1012 in Journal of Natural History 42 (13-14) on page 1009, DOI: 10.1080/00222930701877540, http://zenodo.org/record/5219160